The Effectiveness of e-procurement Implementation for Preventing Fraud in the Government Procurement Goods/ Services (International Conference of Graduate School on Sustainability (ICGSS), 2020)
This research focuses on scrutinizing a series of article concerning the effectiveness of e-procurement implementation for preventing fraud in the government procurement of goods/ services. There had been too many numbers of irregularities in the government procurement of goods/ services prior to the implementation of e-procurement. The implementation of e-procurement is expected to reduce the number of irregularities, so that the ultimate objective of good governance, which is indicated by effectiveness, efficiency, transparency, and accountability, can be achieved. This research employed several methods. After several considerations, a descriptive method with a qualitative approach was particularly selected because it embodied the needs to analyse the effectiveness of e-procurement implementation for preventing fraud in the government procurement of goods/ services.